2013
DOI: 10.1186/1743-422x-10-305
|View full text |Cite
|
Sign up to set email alerts
|

Human rhinoviruses and enteroviruses in influenza-like illness in Latin America

Abstract: BackgroundHuman rhinoviruses (HRVs) belong to the Picornaviridae family with high similarity to human enteroviruses (HEVs). Limited data is available from Latin America regarding the clinical presentation and strains of these viruses in respiratory disease.MethodsWe collected nasopharyngeal swabs at clinics located in eight Latin American countries from 3,375 subjects aged 25 years or younger who presented with influenza-like illness.ResultsOur subjects had a median age of 3 years and a 1.2:1.0 male:female rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 52 publications
4
46
3
Order By: Relevance
“…9,38,39 HRVs and HEVs were detected more frequently in children aged < 5 year (35.4% and 21.2%, respectively). These results are in concordance with those of other studies, which concluded that children of 5 years of age or younger had a higher risk of infection by HRV and HEV, 9,40 although the risk is slighter lower for HEV. Feikin and others (2013) studied Kenyan children under 5 years of age, who had severe acute respiratory infection (SARI).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,38,39 HRVs and HEVs were detected more frequently in children aged < 5 year (35.4% and 21.2%, respectively). These results are in concordance with those of other studies, which concluded that children of 5 years of age or younger had a higher risk of infection by HRV and HEV, 9,40 although the risk is slighter lower for HEV. Feikin and others (2013) studied Kenyan children under 5 years of age, who had severe acute respiratory infection (SARI).…”
Section: Discussionmentioning
confidence: 99%
“…46,47 A more recent study from Latin America shows that HRV and HEV circulate regularly all year long, but show greater activity during the rainy season. 9 Findings from temperate regions show an increase in HRV/ HEV activity during the summer, 48 peaking from July until the beginning of the fall, followed by a slow decline. However, monitoring must continue for several years if we are to provide a more detailed analysis of the seasonality of these viruses in a sub-Saharan context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species has adapted to urban areas, occupying roofs, ceilings, and other human constructions, and often coexists with other bat species and humans (2), enabling epidemiologic risks (3). In recent studies, an alphacoronavirus has been detected in urban bat species Molossus molossus, M. rufus, and Tadarida brasiliensi in Brazil (4,5).…”
mentioning
confidence: 99%